Penelitian Permainan Rakyat: Konten Analisis (Content Analysis) Pada Website Garuda RISTEK-BRIN - Evi Nursanti Rukmana; Samson CMS; Kusnandar Kusnandar (IAIN Ponorogo, 2021)
The folk games are the one development of object culture to must to the preserve. The researcher has researched traditional games from science various. The purpose this research to know folk games research through content analysis in Garuda RISTEK-BRIN website. The research method use analysis content with qualitative approach. The data collection through literature study from 13 folk games research. Based on result analysis found 5 sub themes consist of architecture desain, the type of traditional games analysis, school teaching materials, song traditional games analysis, and traditional games transformation. The research based on publication year has various year publication. The experience of publication year ups and down after sorted using journal names from the initial letters of journal names a to s. The language used in this study uses Indonesian with differences in the writing of the title, the use of Indonesian English titles, Indonesian titles, and Indonesian English titles. The research 13 studies has 63 types of traditional games with the number of games reaching 77. Folk games from an area become a cultural representation of the area itself. Hopefully this research will provide benefits for the reference and development of the next folk game research.